â€œGelandanganâ€ Karya Slamet Abdul Sjukur dalam Perspektif Estetika Keburukan sebagai Kritik terhadap Estetika Musik Konvensional - Eddo Diaz Rinaldo (Institut Seni Indonesia Denpasar, 2021)
Purpose: This research is meant to re-study the work of Slamet Abdul Sjukur, â€œGelandanganâ€ using the Aesthetic of Ugliness. Also to study how far the correlation between this aesthetic with conventional musical aesthetic. Research methods: This research is using qualitative method with some descriptic interpretative analytical technic, and literature study as the data collection method. Results and discussion: It was found a new perspective that still rellevant and capable to be use to study the aesthetic value of the conceptual works such as â€œGelandanganâ€. Moreover, some works with similar aesthtetic patterns will be more traceable and the value will be more musically recognised using this Aesthetic of Ugliness perspective. Even with the aspect of Amorphousness, Assymetry, and Disharmony, the beauty of the piece can be presented in a whole new different shape. Implication: Furthermore, the writer will throw some another issues that spread out through society, about the benefits and risks that raised from this piece of work.